Pre-Columbian Goldsmithing: Categories of Analysis in the Theses of the School of Plastic Arts (1953-1977) - Lizano Quesada, Ana Catalina (2019)
At the University of Costa Rica pre-Columbian goldsmithing has been explored from different fields, including archeology, history, cultural identity, architecture and art. The present study seeks to reconstruct the knowledge generated, exclusively, from the theses made in the School of Plastic Arts. The categories of analysis used by the researchers are revealed and the variants found in the approach of the object of study are examined. We present contextual data about this practice at the School of Plastic Arts and on the current state of the specialty, some reflections are developed around the validity of goldsmithing in this institution and its scope.